CAPITAL PUNISHMENT IN INDIA - Thulasiraman, Dr J (Innovative Research Thoughts, 2017)
The death penalty is a legitimate punishment in India. It has been completed in five occurrences since 1995, while a sum of twenty-six executions have occurred in India since 1991, the latest of which was in 2015. The Supreme Court in Mithu versus Territory of Punjab struck down Section 303 of the Indian Penal Code, which accommodated a required capital punishment for guilty parties who submitted murder while serving a lifelong incarceration. The quantity of individuals executed in India since the country accomplished Independence in 1947 involves question; official government measurements guarantee that fifty-two individuals had been executed since Independence.